2021
DOI: 10.1002/chem.202100791
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Perturbations from the Protein Affect C−H Bond Strengths of the Substrate and Enable Negative Catalysis in the TmpA Biosynthesis Enzyme

Abstract: The nonheme iron dioxygenase 2‐(trimethylammonio)‐ethylphosphonate dioxygenase (TmpA) is an enzyme involved in the regio‐ and chemoselective hydroxylation at the C1‐position of the substrate as part of the biosynthesis of glycine betaine in bacteria and carnitine in humans. To understand how the enzyme avoids breaking the weak C2−H bond in favor of C1‐hydroxylation, we set up a cluster model of 242 atoms representing the first and second coordination sphere of the metal center and substrate binding pocket, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 128 publications
0
29
0
Order By: Relevance
“…50 However, for an isolated 2-(trimethylammonio)ethylphosphonate molecule in the gas phase a homolytic BDE C 1 −H = 96.1 kcal mol −1 was calculated, while the C 2 −H bond energy is significantly less, namely, BDE C 2 −H = 91.5 kcal mol −1 . 47 Therefore, based on the relative values of the BDEs for the C 1 −H and C 2 −H bonds, a regioselective C 2 -hydroxylation would be expected; however, the products distributions only find C 1 -hydroxylation instead. Previously, for a large test set of chemical compounds, we showed that the bond dissociation energy is linearly related to the change in polarizability along that chemical bond and consequently bond energies may be affected by electric field perturbations.…”
Section: Electric Field Affecting Substrate Bond Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…50 However, for an isolated 2-(trimethylammonio)ethylphosphonate molecule in the gas phase a homolytic BDE C 1 −H = 96.1 kcal mol −1 was calculated, while the C 2 −H bond energy is significantly less, namely, BDE C 2 −H = 91.5 kcal mol −1 . 47 Therefore, based on the relative values of the BDEs for the C 1 −H and C 2 −H bonds, a regioselective C 2 -hydroxylation would be expected; however, the products distributions only find C 1 -hydroxylation instead. Previously, for a large test set of chemical compounds, we showed that the bond dissociation energy is linearly related to the change in polarizability along that chemical bond and consequently bond energies may be affected by electric field perturbations.…”
Section: Electric Field Affecting Substrate Bond Strengthsmentioning
confidence: 99%
“…44−46 Several examples of the substrates and reaction products obtained for these biosynthesis enzymes are given in Figure 2 with the respective BDE values of calculated C−H bond strengths. 26,39,43,47,48 Thus, prolyl-4-hydroxylase (P4H) chemoand enantioselectively hydroxylates the C 4 -position of a proline residue in a peptide chain to form R-4-hydroxyproline, an essential component of collagen strands that gives it its structure and function. 38 A series of computational studies on P4H, however, actually showed that the C 5 −H bonds in proline are significantly weaker than the C 4 −H bonds and hence C 5hydroxylation should be the dominant reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, computational studies on the biosynthesis nonheme iron dioxygenase HygX identified a positively charged active site Lys residue that through charge-dipole interactions influences reactivity patterns and guides the selectivity of the reaction . However, in the analogous enzymes viomycin biosynthesis enzyme (VioL), the 2-(trimethylammonio)­ethylphosphonate dioxygenase (TmpA) and the carbon starvation-induced protein D (CsiD), a combination of positively and negatively charged residues arranged local dipole moments in such a way that an otherwise unfavorable reaction pathway was stabilized. These long-range interactions were shown to affect redox potentials and bond strengths and hence influence the catalytic cycle and enzymatic turnover. To understand the technical details of second- and first-coordination sphere effects of enzymes, many inorganic chemists have made links of enzymatic structures with synthetic (biomimetic) models.…”
Section: Second-coordination Sphere Effectsmentioning
confidence: 99%
“…Hence, we will focus on the mechanism starting from CpdI and a substrate only. Previous studies of ours showed that large QM cluster models of well over 150 atoms represent the oxidant and substrate binding pockets of enzymes highly accurately and give results at par with QM/MM methods [43][44][45][46]. Therefore, a large QM cluster model of the substrate-bound P450 OleT models was set up.…”
Section: Resultsmentioning
confidence: 99%